Original paperExperience in percutaneous atrial septal defects closure after previous cardiac surgery - Fiszer, Roland; Szkutnik, Małgorzata; Kusa, Jacek; Białkowski, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2008)
Introduction: Atrial septal defect (ASD) makes up 6-8% of congenital heart defects. Results of surgical correction are good with low mortality, but 1-1.5% of patients have residual shunt requiring intervention. Material and methods: In years 1996-2008 we performed 21 percutaneous residual ASD closures after cardiac surgery. First group – 7 patients after surgical ASD closures; second group – 14 patients after cardiac surgery other than ASD closure with residual IAS shunt. Results: In the first group 6 ASO devices 8-24 mm and in one patient Amplatzer Cribriform 25 mm were used. In the second group as primary surgery were tetralogy of Fallot and correction of right ventricular outflow tract obstruction – 6 patients, Fontan fenestration – 4 patients. One patient – with Ebstein anomaly after cavo-pulmonary shunt, ventricular septal defect (VSD), and transposition of great arteries (TGA) correction and CABG procedure. In 12 of 14 patients 5-30 mm Amplatzer Septal Occluder (ASO), in one case Star-Flex 33 mm and IMWCE-5-PDA-3 coil were used. Patients with right-left shunt presented a significant (77 to 90%) rise in arterial blood saturation directly after the procedure. Conclusions: Percutaneous residual interatrial septum (IAS) shunt closure in patients after previous surgical ASD correction or other cardiac surgery procedures is not difficult technically and the results are satisfactory.